Vliv rybího oleje na sekreci a úcinek inzulínu u nemocných s diabetem II. typu - Pelikánová, T; Kohout, M; Válek, J; Kazdová, L; Karasová, L; Base, J; Stefka, Z (Casopis lekaru ceskych, 1992)
The metabolic effect of 3-week dietary supplementation with a fish oil concentrate was examined in not markedly obese, not hypertriglyceridemic men with non-insulin-dependent diabetes mellitus (NIDDM) treated with hypoglycemic agents. Ten patients were given 15 ml/d of fish oil (Martens Oil, Norway) equivalent to 3.1 g of n-3 fatty acid (FA) per day, and compared to 10 diabetics treated with placebo (15 ml/d saline). While fish oil leads to expected increase in the ratio of n-3 to n-6 FA intake, it does not alter fasting and mixed meal stimulated blood glucose, plasma insulin and C-peptide concentrations. There were no changes in insulin action estimated by the metabolic clearance rates of glucose at plasma insulin levels of about 100 microU/ml and 1400 microU/ml during hyperinsulinemic isoglycemic clamp, and no changes were seen in insulin binding to erythrocytes. Even though our short-term study does not warrant authoritative conclusions, no adverse effects of low-dose fish oil on glucose homeostasis have been found in not markedly obese NIDDM patients treated with oral hypoglycemics.
Keywords: Diabetes Mellitus, Type 2; Fish Oils; Adult; dospělí; Humans; mužské pohlaví; Male; lidé; diabetes mellitus 2. typu; lidé středního věku; Insulin; Middle Aged; Glucose; rybí oleje; glukosa; inzulin